DIPLOMASI AUSTRALIA-INDONESIA DALAM PEMBERIAN GRASI TERHADAP TERPIDANA KASUS NARKOBA (SCHAPELLE LEIGH CORBY) TAHUN 2009-2014 - Lathifah, Hasna; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study analyzes the case of Schapelle Leigh Corby , an Australian citizen who was caught smuggling four kilograms of marijuana to be smuggled into Indonesia through Ngurah Rai airport Denpasar After serving a sentence of less than seven years , the Indonesian government gave clemency or pardons to Corby as much as five years in prison . Filing by the attorney Corby clemency was done because he declared mentally ill by two different doctors . In granting clemency to Corby pour a lot of protests from the public, since the middle of Susilo's administration was keen to fight the drug problem giving Corby clemency to prisoners who are drug related problems.This research uses qualitative research methods. Research conducted by way of explaining based on existing data. Then techniques used in this research libraries from various sources such as books, journals,newspapers and also the documentation is accessible from the internet. The theory used in this research is the theory of diplomacy by Nicolson and the concept of multitrack diplomacy by Dr. Louise Diamond and John McDonald.The result is the an exemption of a narcotic prisoner, an Australian citizen, Schepelle Leigh Corby, cause a dissent among the people in Indonesia. Many of the people oppose those exemption. That opposition happens cause of an indication that there is an agreement between Indonesia and Australia government. If we observe it, those exemption has some benefits for the people and Indonesia government. For the state and Indonesia governement those exemption could improve a relationship between the states, as well as means to facing the political developments of South Pasific regions in the future.Keywords: diplomacy,multitrack diplomacy, granting clemency.